2004
DOI: 10.1042/bj20031714
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide sensitizes astrocytes to oxidative stress: protective role of cannabinoids

Abstract: Cannabinoids induce apoptosis on glioma cells via stimulation of ceramide synthesis de novo, whereas they do not affect viability of primary astrocytes. In the present study, we show that incubation with Delta9-tetrahydrocannabinol did not induce accumulation of ceramide on astrocytes, although incubation of these cells in a serum-free medium (with or without cannabinoids) led to stimulation of ceramide synthesis de novo and sensitization to oxidative stress. Thus treatment with H2O2 induced apoptosis of 5-day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 37 publications
0
40
0
3
Order By: Relevance
“…53 Previously, cannabinoids have been reported to cause heterogeneous changes to the growth and survival of tumour cells. These changes include alterations to the cell cycle, resulting in growth arrest, 54,55 the induction of apoptosis, 16,56 nonapoptotic cell death, 19 necrosis, 57 and in some instances the promotion of cell proliferation. 53 Interestingly, we found that relatively low concentrations of THC were required to cause a considerable reduction in colorectal cancer cell survival (i.e., 7.5-12.5 lM), which is comparable with the concentrations of THC required to elicit antitumoral responses in other epithelial cells, such as breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…53 Previously, cannabinoids have been reported to cause heterogeneous changes to the growth and survival of tumour cells. These changes include alterations to the cell cycle, resulting in growth arrest, 54,55 the induction of apoptosis, 16,56 nonapoptotic cell death, 19 necrosis, 57 and in some instances the promotion of cell proliferation. 53 Interestingly, we found that relatively low concentrations of THC were required to cause a considerable reduction in colorectal cancer cell survival (i.e., 7.5-12.5 lM), which is comparable with the concentrations of THC required to elicit antitumoral responses in other epithelial cells, such as breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The protective effect of cannabinoids against oxidative stress in vitro in neurons is dependent on their anti-oxidant properties as cannabinoid receptors are not involved in this process [157,158]. However, in astrocytes, the CB1 receptor mediates the protective effect of cannabinoids, because cannabinoids prevented H 2 O 2 -induced loss of viability of astrocytes in cell culture in a CB1-receptor-dependent manner [159]. For the neuroprotective effect of cannabinoids both their anti-oxidant and receptor binding properties contribute, as was shown in a rodent model of Parkinson's disease [160,161].…”
Section: The Cannabinoid System Modulates Age-related Molecular and Cmentioning
confidence: 99%
“…However, de novo ceramide can be associated with apoptotic sensitization after oxidative stress [11]. The oxidative stress inducer photodynamic therapy uses a photosensitizer, visible light and oxygen to generate reactive oxygen species that can destroy malignant cells by apoptosis [12,13].…”
Section: Introductionmentioning
confidence: 99%